Self‐Powered Wireless Sensor Node Enabled by a Duck‐Shaped Triboelectric Nanogenerator for Harvesting Water Wave Energy. Issue 7 (8th December 2016) - Ahmed, Abdelsalam; Saadatnia, Zia; Hassan, Islam; Zi, Yunlong; Xi, Yi; He, Xu; Zu, Jean; Wang, Zhong Lin
Abstract : This paper presents a fully enclosed duck‐shaped triboelectric nanogenerator (TENG) for effectively scavenging energy from random and low‐frequency water waves. The design of the TENG incorporates the freestanding rolling mode and the pitch motion of a duck‐shaped structure generated by incident waves. By investigating the material and structural features, a unit of the TENG device is successfully designed. Furthermore, a hybrid system is constructed using three units of the TENG device. The hybrid system achieves an instantaneous peak current of 65.5 µA with an instantaneous output power density of up to 1.366 W m −2 . Following the design, a fluid–solid interaction analysis is carried out on one duck‐shaped TENG to understand the dynamic behavior, mechanical efficiency, and stability of the device under various water wave conditions. In addition, the hybrid system is experimentally tested to enable a commercial wireless temperature sensor node. In summary, the unique duck‐shaped TENG shows a simple, cost‐effective, environmentally friendly, light‐weight, and highly stable system. The newly designed TENG is promising for building a network of generators to harvest existing blue energy in oceans, lakes, and rivers. Abstract : A duck‐shaped triboelectric nanogenerator (TENG) for effectively scavenging energy from random and low‐ frequency water waves is presented. The design of the TENG incorporates the freestanding rolling mode and the pitch motion of a duck‐shaped structure generated by incident waves. The newly designed TENG is promising for building a network of generators to harvest existing blue energy in oceans, lakes, and rivers.